Nghiên cứu quan hệ chế độ làm sạch và độ bền bám các màng bảo vệ - Trần, Đình Tường (Hà Nội, 2013)
Using the Strickness - Instrument QH3 and on physical Base of Clining in low Vakuum to study the Solid - Strickness of the thin Films MgF2; SiO with optical Thickness n1. d=λ/4; 3λ/4 ; 5λ/4;... on Surfaces of optical Elements.